A homozygous female hemophilia A - Nair, Preethi S. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Hemophilia A (HA), being an X-linked recessive disorder, females are rarely affected, although they can be carriers. AIMS: To study the mutation in F8 gene in an extended family with a homozygous female HA. MATERIALS AND METHODS: All the seven affected members (six males and one female) were initially screened by Conformation Sensitive Gel Electrophoresis (CSGE) and direct DNA sequencing. RESULTS: A homozygous missense mutation c.1315G>A (p.Gly420Ser) was identified in exon 9 of F8 gene in homozygous state in the affected female born of 1° consanguinous marriage and in all the affected male members of the family. Her factor VIII levels was found to be 5.5%, vWF:Ag 120%. CONCLUSION: In India, as consanguineous marriages are very common in certain communities (up to 30%), the likelihood of encountering female hemophilia is higher, although this is the first case of HA out of 1600 hemophilia families registered in our Comprehensive Haemophilia Care Center. Genetic diagnosis in such cases is not necessary as all the male children will be affected and daughters obligatory carriers.